"It was like I had to fit into a category": Care-seekers' experiences of gender regulation in the Swedish trans-specific healthcare. (January 2019) - Linander, Ida; Alm, Erika; Goicolea, Isabel; Harryson, Lisa
The few previous studies investigating regulation of gender in trans-specific healthcare are mainly based on text material and interviews with care-providers or consist solely of theoretical analyses. There is a lack of studies analysing how the regulation of gender is expressed in the care-seeker's own experiences, especially in a Nordic context. The aim of this study is to analyse narratives of individuals with trans experiences (sometimes called transgender people) to examine how gender performances can be regulated in trans-specific care in Sweden. The conceptual framework is inspired by trans studies, a Foucauldian analysis of power, queer phenomenology and the concept of cisnormativity. Fourteen interviews with people with trans experiences are analysed with constructivist grounded theory. The participants' experiences indicate that gender is constructed as norm-conforming, binary and stable in trans-specific healthcare. This gendered position is resisted, negotiated and embraced by the care-seekers. Norms and discourses both inside and outside trans-specific care contribute to the regulation and limit the room for action for care-users. We conclude that a trans-specific care that has a confirming approach to its care-users, instead of the current focus on gender norm conformity, has the potential to increase the self-determination of gender performance and increase the quality of care.